A method for preparing a noble metal-sensitized nanoporous SnO2-based gas-sensitive material
Through the assembly technology of diol and amphiphilic block copolymer, large-porous nanoporous SnO2-based gas-sensitive material is formed, which solves the problems of slow response and poor stability of SnO2 semiconductor gas-sensitive materials, and achieves high-efficiency gas-sensitive performance and low cost Industrialized production.
Patent Information
- Application Number
- CN202210365991.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-08
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-04-08
AI Technical Summary
The existing SnO2 semiconductor gas-sensitive materials respond slowly, have a long recovery time and poor stability in gas sensing. The synthesis cost of nanoporous SnO2 is high and the yield is low. The material framework is prone to collapse when calcined at high temperature, resulting in large-porous nanoporous oxidation. Tin synthesis is difficult.
Using diols as solvents and metal precursor modifiers, and amphiphilic block copolymers as structural inducers, nanoporous SnO2-based gas-sensitive materials with large pore sizes are assembled through chelation and reverse phase composite micelles to ensure that Skeleton integrity and improves the sensitization properties of the material.
It realizes the acquisition of large-porous nanoporous SnO2-based gas-sensitive materials under the premise of low cost and high yield, significantly improves gas-sensitive performance, reduces working temperature, enhances response and recovery time, and is suitable for a variety of toxic and harmful gases. Test.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of advanced porous nanomaterials, and in particular relates to a method for preparing a noble metal-sensitized nanoporous SnO2-based gas-sensitive material. Background Art
[0002] As a typical n-type semiconductor, tin oxide is a commonly used metal oxide semiconductor gas-sensitive material with properties such as high electron mobility, wide bandgap, non-stoichiometry, and good thermal stability. However, when single-component SnO2 semiconductor gas-sensitive materials are used for gas sensing, there are problems such as slow response, long recovery time, and poor stability.
[0003] In the prior art, strategies to improve the gas-sensing performance of SnO2 semiconductor materials include three directions: first, modifying its components, such as modifying with precious metals. For example, Chinese patent publication number CN112225255A discloses an ordered double-mesoporous metal oxide composite material loaded with precious metals and its preparation method; second, SnO2 is composited with one or more metal oxides to construct a heterojunction. The heterojunction can effectively accelerate the transmission of electrons, and can also enhance oxygen adsorption, form abundant oxygen vacancies, and provide new active sites for the reaction, thereby significantly improving the gas-sensing performance; third, a porous structure is constructed on the bulk SnO2 gas-sensitive material.
[0004] Although studies have reported the synthesis of nanoporous SnO2, due to the fast hydrolysis and polymerization rates of common SnO2 precursors such as SnCl4, SnCl2, etc., a large amount of organic solvents and acid-base catalysts are usually required to regulate the hydrolysis and polymerization process of the metal oxide precursors, and strictly control the synthesis conditions such as environmental humidity, reaction temperature, and hydrolysis time. This results in high synthesis costs and low yields for mesoporous SnO2, which greatly limits its industrial application. In addition, in the synthesis process of traditional nanoporous SnO2, when the template is removed by high-temperature calcination, the material skeleton is very likely to shrink and reorganize, resulting in the collapse of the entire mesoporous skeleton. Therefore, the synthesis of large-pore nanoporous tin oxide still faces huge challenges. Summary of the invention
[0005] In view of the above problems, an embodiment of the present invention provides a method for preparing a precious metal-sensitized nanoporous SnO2-based gas-sensitive material. By modifying the solvent and the metal precursor, the reaction parameters and process can be better controlled. The method is simple, controllable, and universal, and can be easily industrialized. At the same time, the volume of the small molecules of the inorganic tin salt is increased, so that a huge reverse composite micelle is formed when the chelate and the amphiphilic block copolymer are assembled, which can significantly inhibit the hydrolysis of the tin oxide precursor, thereby increasing the pore size while ensuring the integrity of the skeleton and improving the sensitization performance of the material.
[0006] In order to achieve the above purpose, the embodiment of the present invention adopts the following technical solution:
[0007] A method for preparing a noble metal-sensitized nanoporous SnO2-based gas-sensitive material, comprising:
[0008] A diol is used as a solvent and a metal precursor modifier, and an amphiphilic block copolymer is used as a structure inducing agent, wherein the hydrophilic block is a polymer that can interact with the SnO2 precursor through electrostatic interaction, coordination interaction and / or hydrogen bonding interaction;
[0009] When the structure inducing agent co-assembles the SnO2 precursor and the noble metal precursor, the diol first chelates with the SnO2 precursor and the noble metal precursor to form a metal chelate, and then forms a reverse composite micelle with the amphiphilic block copolymer;
[0010] When the solvent evaporates after the assembly is completed, the reverse composite micelles further accumulate to form a super-large molecular assembly, providing a skeleton for calcination, and after calcination to remove the structural inducer, large-pore nanoporous materials are obtained to obtain precious metal-sensitized nanoporous SnO2-based gas-sensitive materials.
[0011] The nanoporous SnO2-based gas-sensitive material includes a nanoporous SnO2 gas-sensitive material and a nanoporous SnO2-based gas-sensitive material composited with other metal oxides.
[0012] Among them, the diol and the SnO2 precursor undergo chelation to form a metal chelate, which can not only inhibit the hydrolysis of the inorganic tin salt as the SnO2 precursor, promote the full self-assembly of the inorganic tin salt and the amphiphilic block copolymer, but also increase the volume of the small molecules of the inorganic tin salt, so that when the chelate is assembled with the amphiphilic block copolymer, a reverse composite micelle is formed through the microphase separation of the amphiphilic block copolymer. During the evaporation of the solvent, the reverse composite micelle is further accumulated to form a super-macromolecular assembly. After calcination to remove the block copolymer, a precious metal-sensitized nanoporous SnO2-based gas-sensitive material is obtained, and the obtained nanoporous material has a large pore size. When the metal oxide precursor only contains SnO2 precursor, a single-component ordered large-pore mesoporous SnO2 gas-sensitive material is obtained; when the metal oxide precursor includes other metal oxide precursors in addition to the SnO2 precursor, such as one or more metal oxide precursors of nickel oxide, zinc oxide, tungsten oxide, niobium oxide, zirconium oxide, titanium oxide, etc., an ordered large-pore mesoporous gas-sensitive material composite of SnO2 and other metal oxides is obtained. This composite material has a heterojunction structure between multiple metals.
[0013] Among them, reverse composite micelles and ultra-large molecular assemblies can eventually obtain large-aperture mesopores. The order of the mesopores makes them have uniform and open nanopores, which is beneficial to the directional transmission of electrons in the reaction process; large pores can obtain high specific surface area, large pore volume, adjustable chemical composition and surface properties, can provide more active sites, and are beneficial to gas-solid interface gas-sensitive catalysis; highly interconnected large-aperture channels are beneficial to the diffusion and mass transfer of gas in sensitive materials, increase the probability of gas-sensitive material interface reaction, and are beneficial to the adsorption of gas molecules and the catalytic reaction, thereby significantly improving gas sensing sensitivity and reducing detection limits; based on the sensitizing precious metals loaded on large-aperture nanopores, chemical sensitization, electronic sensitization and heterojunction construction can be increased, thereby significantly reducing the operating temperature, improving sensitivity and response / recovery time, and improving gas sensing performance and selectivity.
[0014] In a preferred embodiment of the present invention, the precious metal includes one or an alloy of two or more of platinum, palladium, gold, silver, rhodium, ruthenium, osmium, and iridium.
[0015] In a preferred embodiment of the present invention, the method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material comprises the following specific steps:
[0016] Step S1, adding inorganic tin salt and noble metal precursor to diol solvent, stirring for 5 to 20 minutes to form a uniform first mixed solution; wherein the mass ratio of inorganic tin salt to diol solvent is 1:5 to 1:20, and the mass percentage of the added noble metal precursor to the inorganic tin salt is 0.5wt% to 2wt%.
[0017] Step S2, adding the amphiphilic block copolymer and the concentrated acid solution to the first mixed solution, stirring for 1 to 2 hours, to obtain a second mixed solution; wherein the mass ratio of the amphiphilic block copolymer to the inorganic tin salt is 1:5 to 1:1, and the mass ratio of the concentrated acid solution to the inorganic tin salt is 1:1 to 1:5;
[0018] Step S3, transferring the second mixed solution to a culture dish, placing it at 25-70° C. to volatilize the solvent, transferring it to an oven at 100-150° C. after 10-24 hours, and curing it for 10-24 hours to obtain a uniform transparent film, scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0019] Step S4, transferring the first powder to a tube furnace, heating the temperature to 300-400° C. at a heating rate of 1-5° C. / min under a N2 atmosphere, and calcining for 1-3 hours to obtain a second powder;
[0020] Step S5, transferring the second powder to a muffle furnace, heating the temperature to 350-500° C. at a heating rate of 5-10° C. / min in air, and calcining for 1-3 hours to obtain a noble metal-sensitized nanoporous SnO2 gas-sensitive material.
[0021] In a preferred embodiment of the present invention, the method for preparing the precious metal-sensitized nanoporous SnO2-based gas-sensitive material includes steps S1 to S5 as above, except that in step S1, inorganic tin salt, inorganic zinc salt and precious metal precursor are simultaneously added to a diol solvent; in step S5, a precious metal-sensitized nanoporous SnO2-based ZnO composite gas-sensitive material is obtained.
[0022] In a preferred embodiment of the present invention, the ZnO in the above step S1 and step S5 can be replaced by one or two of nickel oxide, tungsten oxide, niobium oxide, zirconium oxide, and titanium oxide.
[0023] Preferably, the diol solvent used in the above embodiments can be a diol with a carbon number of 2 to 12, specifically selected from one or more of ethylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,10-decanediol, and 1,12-dodecanediol; the inorganic tin salt used can be one of tin tetrachloride, stannous chloride, stannous sulfate, sodium stannate, and the like.
[0024] Preferably, the concentrated acid solution used in the above embodiment can be one or more of concentrated hydrochloric acid, concentrated nitric acid, concentrated sulfuric acid, etc.; the amphiphilic block copolymer used can be a diblock, triblock or multiblock copolymer, with a number average molecular weight of 5000 to 60000. Wherein the hydrophilic block is a polymer that can interact with inorganic tin salts through electrostatic action, coordination action, hydrogen bonding or other forces, with a number average molecular weight of 1000 to 10000, specifically selected from polyoxyethylene (PEO), poly (N-isopropylacrylamide) (PNIPAM), polyacrylamide (PAM), poly-(2-vinylpyridine) (P2VP), poly-(4-vinylpyridine) (P4VP) One or more; the hydrophobic block is a polymer with hydrophobic properties, with a number average molecular weight between 4000-50000, specifically selected from polystyrene (PS), polypropylene oxide (PPO), polybutadiene (PB), polymethyl methacrylate (PMMA) One or more.
[0025] The noble metal-sensitized nanoporous SnO2-based gas-sensitive material obtained by the above preparation method has a specific surface area of 80 m 2 ·g -1 ~200m 2 ·g -1, pore size is 15nm~50nm, pore volume is 0.1cm 3 ·g -1 ~1.5cm 3 ·g -1 The size of the precious metal nanoparticles is 1 to 5 nm, and they are uniform in size and highly dispersed.
[0026] The noble metal-sensitized nanoporous SnO2-based gas-sensitive material obtained by the above preparation method has an ordered mesoscopic structure, and its pore shape is a kind of vertically divergent tubular pores, spherical pores, and worm-like pores. Its pore structure is P6mm, P63 / mmc, One or more of .
[0027] The precious metal-sensitized nanoporous SnO2-based gas-sensitive material obtained by the above preparation method can be used for gas sensing of toxic and harmful gases (CO, H2S, etc.), volatile organic compounds VOCs (benzene, formaldehyde, etc.), human exhaled gases (acetone, NH3, etc.) and flammable and explosive gases (CH4, H2), and has excellent gas-sensing properties.
[0028] Compared with the prior art, the present invention has the following beneficial technical effects:
[0029] (1) The method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material increases the chelating effect by adding a modifier to adjust the co-assembly rate of the precursor under the structure inducing agent and form large micelles. The method has low requirements for synthesis conditions, and the reaction is relatively thorough and the yield is high, which is easy to realize industrial production.
[0030] (2) The method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material increases the size of the micelles by chelation, provides a solid and stable skeleton for the calcination process, maintains the skeleton structure of the material when the template is removed, and at the same time, the large-sized micelles obtain nanoporous with large pores, thereby ensuring the improvement of the sensitization performance;
[0031] (3) The method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material can also flexibly adjust the pore size by adjusting the type, molecular weight and hydrophilic / hydrophobic segment ratio of the amphiphilic block copolymer, and can also adjust the pore wall thickness by changing the ratio of the SnO2 precursor to the amphiphilic block copolymer, making it widely applicable to the detection of a variety of toxic, harmful, flammable and explosive gases;
[0032] (4) The preparation method of the noble metal-sensitized nanoporous SnO2-based gas-sensitive material is highly universal and can be applied to the synthesis of any large nanoporous metal oxide with easily hydrolyzed inorganic metal salts as precursors; and the loaded noble metals are uniform in size and highly dispersed.
[0033] Of course, it is not necessary to achieve all the advantages mentioned above at the same time when implementing any method of the present invention. DETAILED DESCRIPTION
[0034] Below, by referring to exemplary embodiments, technical problems, technical solutions and advantages of the present invention are explained in detail. The exemplary embodiments described below are only used to explain the present invention and cannot be interpreted as limiting the present invention. It will be appreciated by those skilled in the art that, unless otherwise defined, all terms (including technical terms and scientific terms) used herein have the same meaning as the general understanding of those of ordinary skill in the field to which the present invention belongs. It should also be understood that those terms such as those defined in general dictionaries should be understood to have a meaning consistent with the meaning in the context of the prior art, and unless defined here, will not be interpreted with an idealized or overly formal meaning.
[0035] Example 1
[0036] This embodiment provides a method for preparing a Pt-sensitized nanoporous SnO2 gas-sensitive material, comprising the following steps:
[0037] Step S1: 200 mg SnCl4 and 0.5 ml of 2 mg·L -1 The chloroplatinic acid solution was added to 1 g of ethylene glycol solvent and stirred for 5 min to form a uniform first mixed solution;
[0038] Step S2, adding 40 mg of amphiphilic block copolymer polyethylene oxide-b-polystyrene (PEO-b-PS, Mn≈25000) and 40 mg of concentrated hydrochloric acid solution to the first mixed solution, stirring for 1 hour to obtain a second mixed solution;
[0039] Step S3, transferring the second mixed solution to a culture dish and placing it at 25° C. to volatilize the solvent, and after 10 hours, transferring it to an oven at 100° C. and curing it for 10 hours to obtain a uniform transparent film, and scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0040] Step S4, transferring the first powder to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 300° C. at a heating rate of 1° C. / min, and calcining for 3 h to obtain a second powder;
[0041] Step S5, transferring the second powder to a muffle furnace, heating the temperature to 350° C. at a heating rate of 5° C. / min in air, and calcining for 3 hours to obtain a Pt-sensitized nanoporous SnO2 gas-sensitive material.
[0042] The obtained Pt-sensitized nanoporous SnO2 gas-sensitive material has a specific surface area of 84 m 2 ·g -1 , pore size is 23nm, pore volume is 0.3cm 3 ·g -1 The size of the precious metal nanoparticles is 3.8nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0043] Example 2
[0044] This embodiment provides a method for preparing a Pd-sensitized nanoporous SnO2 / NiO gas-sensitive material, comprising the following steps:
[0045] Step S1, 200 mg SnCl2, 200 mg NiCl2 and 1 ml of 2 mg·L -1 The potassium hexachloropalladate solution was added to 2 g of 1,3-propylene glycol solvent and stirred for 15 min to form a uniform first mixed solution;
[0046] Step S2, adding 100 mg of amphiphilic triblock copolymer polyethylene oxide-polypropylene oxide-polyethylene oxide (PEO-PPO-PEO, Mn≈15000) and 100 mg of concentrated nitric acid solution to the first mixed solution described in step S1, stirring for 1.5 h to obtain a second mixed solution.
[0047] Step S3, transferring the second mixed solution to a culture dish and placing it at 35° C. to volatilize the solvent, after 15 hours, transferring it to an oven at 120° C. and curing it for 12 hours to obtain a uniform transparent film, scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0048] Step S4, transferring the first powder to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 350° C. at a heating rate of 2° C. / min, and calcining for 2 h to obtain a second powder;
[0049] Step S5, transferring the second powder to a muffle furnace, heating the temperature to 400° C. at a heating rate of 8° C. / min in air, and calcining for 2 hours to obtain a Pd-sensitized nanoporous SnO2 / NiO gas-sensitive material.
[0050] The obtained Pd-sensitized nanoporous SnO2 / NiO gas-sensitive material has a specific surface area of 1108 m 2 ·g -1, pore size is 15nm, pore volume is 0.22cm 3 ·g -1 The size of the precious metal nanoparticles is 3.2nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0051] Example 3
[0052] This embodiment provides a method for preparing an Au-sensitized nanoporous SnO2 / ZnO gas-sensitive material, comprising the following steps:
[0053] Step S1, 200 mg SnCl4, 200 mg ZnCl2 and 2 ml of 2 mg·L -1 The chloroauric acid solution was added to 4 g of 1,4-butanediol solvent and stirred for 20 min to form a uniform first mixed solution;
[0054] Step S2, adding 200 mg of amphiphilic block copolymer polyethylene oxide-b-polymethyl methacrylate (PEO-b-PMMA, Mn≈30000) and 200 mg of concentrated nitric acid solution to the first mixed solution described in step S1, stirring for 2 hours to obtain a second mixed solution.
[0055] Step S3, transferring the second mixed solution described in step S2 to a culture dish, placing it at 70° C. to volatilize the solvent, and after 24 hours, transferring it to an oven at 150° C. and curing it for 24 hours to obtain a uniform transparent film, and scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0056] Step S4, transferring the first powder described in step S3 to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 400° C. at a heating rate of 2° C. / min, and calcining for 1 hour to obtain a second powder;
[0057] Step S5, transferring the second powder described in step S4 to a muffle furnace, heating the temperature to 500°C at a heating rate of 10°C / min in air, and calcining for 1 hour to obtain Au-sensitized nanoporous SnO2 / ZnO gas-sensitive material.
[0058] The obtained Au-sensitized nanoporous SnO2 / ZnO gas-sensitive material has a specific surface area of 77 m 2 ·g -1 , pore size is 31nm, pore volume is 0.52cm 3 ·g -1 The size of the precious metal nanoparticles is 3.8nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0059] Example 4
[0060] This embodiment provides a method for preparing a Ag-sensitized nanoporous SnO2 / WO3 gas-sensitive material, comprising the following steps:
[0061] Step S1, adding 200 mg SnCl4, 200 mg WCl6 and 1.5 ml 2 mg·L-1 silver nitrate solution to 3 g 1,5-pentanediol solvent, stirring for 10 min to form a uniform first mixed solution;
[0062] Step S2, adding 70 mg of the amphiphilic block copolymer poly-(4-vinylpyridine)-b-polystyrene (P4VP-b-PS, Mn≈33000) and 100 mg of concentrated nitric acid solution to the first mixed solution described in step S1, stirring for 1.5 h to obtain a second mixed solution.
[0063] Step S3, transferring the second mixed solution described in step S2 to a culture dish, placing it at 50° C. to volatilize the solvent, and after 18 hours, transferring it to an oven at 130° C. and curing it for 18 hours to obtain a uniform transparent film, and scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0064] Step S4, transferring the first powder described in step S3 to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 350° C. at a heating rate of 2° C. / min, and calcining for 2 h to obtain a second powder;
[0065] Step S5, transferring the second powder described in step S4 to a muffle furnace, heating the temperature to 450°C at a heating rate of 5°C / min in air, and calcining for 2h to obtain an Ag-sensitized ordered macroporous mesoporous SnO2 / WO3 gas-sensitive material.
[0066] The obtained Ag-sensitized nanoporous SnO2 / WO3 gas-sensitive material has a specific surface area of 128 m 2 ·g -1 , the pore size is 27nm, and the pore volume is 0.46cm 3 ·g -1 The size of the precious metal nanoparticles is 4.0nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0067] Example 5
[0068] This embodiment provides a method for preparing a Rh-sensitized nanoporous SnO2 / ZrO2 gas-sensitive material, comprising the following steps:
[0069] Step S1: 200 mg SnCl4, 200 mg ZrCl4 and 1 ml of 2 mg·L -1 The potassium hexachlororhodate solution was added to 2 g of ethylene glycol solvent and stirred for 20 min to form a uniform first mixed solution;
[0070] Step S2, adding 50 mg of the amphiphilic block copolymer poly-(2-vinylpyridine)-b-polystyrene (P2VP-b-PS, Mn≈50000) and 50 mg of concentrated sulfuric acid solution to the first mixed solution described in step S1, stirring for 2 hours to obtain a second mixed solution.
[0071] Step S3, transferring the second mixed solution in step S2 to a culture dish, placing it at 60° C. to volatilize the solvent, and after 12 hours, transferring it to an oven at 120° C. and curing it for 12 hours to obtain a uniform transparent film, and scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0072] Step S4, transferring the first powder described in step S3 to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 400° C. at a heating rate of 5° C. / min, and calcining for 2 h to obtain a second powder;
[0073] Step S5, transferring the second powder described in step S4 to a muffle furnace, heating the temperature to 500°C at a heating rate of 8°C / min in air, and calcining for 2h to obtain Rh-sensitized ordered macroporous mesoporous SnO2 / ZrO2 gas-sensitive material.
[0074] The obtained Rh-sensitized nanoporous SnO2 / ZrO2 gas-sensitive material has a specific surface area of 72 m 2 ·g -1 , pore size 37nm, pore volume 0.63cm 3 ·g -1 The size of the precious metal nanoparticles is 4.6nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0075] Example 6
[0076] This embodiment provides a method for preparing an Ir-sensitized nanoporous SnO2 / Nb2O5 gas-sensitive material, comprising the following steps:
[0077] Step S1: 200 mg SnCl4, 200 mg NbCl5 and 0.5 ml of 2 mg·L -1 The chloroiridic acid solution was added to 3 g of 1,6-hexanediol solvent and stirred for 10 min to form a uniform first mixed solution;
[0078] Step S2, adding 80 mg of amphiphilic block copolymer polyethylene oxide-b-polystyrene (PEO-b-PS, Mn≈33000) and 60 mg of concentrated hydrochloric acid solution to the first mixed solution described in step S1, stirring for 1 hour, to obtain a second mixed solution.
[0079] Step S3, transferring the second mixed solution described in step S2 to a culture dish, and placing it at 55° C. to volatilize the solvent, and after 20 hours, transferring it to an oven at 110° C. and curing it for 12 hours to obtain a uniform transparent film, and scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0080] Step S4, transferring the first powder described in step S3 to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 300° C. at a heating rate of 1° C. / min, and calcining for 2.5 h to obtain a second powder;
[0081] Step S5, transferring the second powder described in step S4 to a muffle furnace, heating the temperature to 450°C at a heating rate of 5°C / min in air, and calcining for 2h to obtain an Ir-sensitized ordered macroporous mesoporous SnO2 / Nb2O5 gas-sensitive material.
[0082] The obtained Ir-sensitized nanoporous SnO2 / Nb2O5 gas-sensitive material has a specific surface area of 90 m 2 ·g -1 , pore size is 30nm, pore volume is 0.8cm 3 ·g -1 The size of the precious metal nanoparticles is 3nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0083] Example 7
[0084] This embodiment provides a method for preparing a Pt-sensitized nanoporous SnO2 / WO3 / NiO gas-sensitive material, comprising the following steps:
[0085] Step S1: 200 mg SnCl4, 200 mg WCl6, 200 mg NiCl2 and 1 ml 2 mg·L -1 The chloroplatinic acid solution was added to 2 g of ethylene glycol solvent and stirred for 20 min to form a uniform first mixed solution;
[0086] Step S2, adding 50 mg of amphiphilic block copolymer polyethylene oxide-b-polystyrene (PEO-b-PS, Mn≈35000) and 50 mg of concentrated hydrochloric acid solution to the first mixed solution described in step S1, stirring for 2 hours to obtain a second mixed solution.
[0087] Step S3, transferring the second mixed solution described in step S2 to a culture dish, placing it at 40° C. to volatilize the solvent, and after 24 hours, transferring it to an oven at 100° C. and curing it for 12 hours to obtain a uniform transparent film, scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0088] Step S4, transferring the first powder described in step S3 to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 350° C. at a heating rate of 2° C. / min, and calcining for 2 h to obtain a second powder;
[0089] Step S5, transferring the second powder described in step S4 to a muffle furnace, heating the temperature to 500°C at a heating rate of 5°C / min in air, and calcining for 1 hour to obtain a Pt-sensitized ordered macroporous mesoporous SnO2 / WO3 / NiO gas-sensitive material.
[0090] The obtained Pt-sensitized nanoporous SnO2 / WO3 / NiO gas-sensitive material has a specific surface area of 76 m 2 ·g -1 , pore size is 28nm, pore volume is 0.3cm 3 ·g -1 The size of the precious metal nanoparticles is 2.0nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0091] Example 8
[0092] This embodiment provides a method for preparing a Pd-sensitized nanoporous SnO2 / ZnO / Nb2O5 gas-sensitive material, comprising the following steps:
[0093] Step S1, 200 mg SnCl4, 200 mg ZnCl2, 200 mg NbCl5 and 2 ml of 2 mg·L -1 The potassium hexachloropalladate solution was added to 1.5 g of 1,3-propylene glycol solvent and stirred for 15 minutes to form a uniform first mixed solution;
[0094] Step S2, adding 100 mg of amphiphilic block copolymer polyethylene oxide-b-polystyrene (PEO-b-PS, Mn≈40000) and 100 mg of concentrated hydrochloric acid solution to the first mixed solution described in step S1, stirring for 1 hour, to obtain a second mixed solution.
[0095] Step S3, transferring the second mixed solution in step S2 to a culture dish, placing it at 45° C. to volatilize the solvent, and after 12 hours, transferring it to an oven at 120° C. and curing it for 12 hours to obtain a uniform transparent film, and scraping the transparent film from the culture dish and grinding it to obtain a first powder;
[0096] Step S4, transferring the first powder described in step S3 to a tube furnace, passing N2 to form an inert atmosphere, heating the temperature to 400° C. at a heating rate of 1° C. / min, and calcining for 1 hour to obtain a second powder;
[0097] Step S5, transfer the second powder described in step S4 to a muffle furnace, increase the temperature to 400°C at a heating rate of 10°C / min in air, and calcine for 3 hours to obtain Pd-sensitized ordered macroporous mesoporous SnO2 / ZnO / Nb2O5 gas-sensitive material.
[0098] The obtained Pd-sensitized nanoporous SnO2 / ZnO / Nb2O5 gas-sensitive material has a specific surface area of 46 m 2 ·g -1 , the pore size is 34nm and the pore volume is 0.57cm 3 ·g -1 The size of the precious metal nanoparticles is 5nm, which can effectively detect gases such as CO, H2S, VOCs, and NH3.
[0099] The above is a preferred embodiment of the present invention. It should be noted that the present invention is not limited to the exemplary embodiments disclosed above. The essence of the description is only to help those skilled in the relevant field to comprehensively understand the specific details of the present invention. For those skilled in the art, without departing from the principles of the present invention, several improvements and modifications made within the technical scope disclosed by the present invention, and changes or replacements that can be easily thought of, should be covered within the protection scope of the present invention.
Claims
1. A method for preparing a noble metal-sensitized nanoporous SnO2-based gas-sensitive material, characterized in that: include: A diol is used as a solvent and a metal precursor modifier, and an amphiphilic block copolymer is used as a structure inducing agent, wherein the hydrophilic block is a polymer that can interact with the SnO2 precursor through electrostatic interaction, coordination interaction and / or hydrogen bonding interaction; When the structure inducing agent co-assembles the SnO2 precursor and the noble metal precursor, the diol first chelates with the SnO2 precursor and the noble metal precursor to form a metal chelate, and then forms a reverse composite micelle with the amphiphilic block copolymer under the action of microphase separation to inhibit the hydrolysis of the tin oxide precursor. After the assembly is completed and the solvent is evaporated, the reverse composite micelles are further accumulated to form a super-macromolecular assembly, which provides a skeleton for calcination. After calcination to remove the structural inducer, a large-pore nanoporous material is obtained. The pore size is increased while ensuring the integrity of the skeleton, and a noble metal-sensitized nanoporous SnO2-based gas-sensitive material is obtained. The precious metals include one or alloys of two or more of platinum, palladium, gold, silver, rhodium, ruthenium, osmium and iridium; The specific steps of the preparation method are as follows: Step S1, adding an inorganic tin salt and a noble metal precursor to a diol solvent, stirring for 5 to 20 minutes, to form a uniform first mixed solution; wherein the mass ratio of the inorganic tin salt to the diol solvent is 1:5 to 1:20, and the mass percentage of the added noble metal precursor to the inorganic tin salt is 0.5 wt% to 2 wt%; Step S2, adding the amphiphilic block copolymer and the concentrated acid solution to the first mixed solution, stirring for 1 to 2 hours, to obtain a second mixed solution; wherein the mass ratio of the amphiphilic block copolymer to the inorganic tin salt is 1:5 to 1:1, and the mass ratio of the concentrated acid solution to the inorganic tin salt is 1:1 to 1:5; Step S3, transferring the second mixed solution to a culture dish, placing it at 25-70° C. to volatilize the solvent, transferring it to an oven at 100-150° C. after 10-24 hours, and curing it for 10-24 hours to obtain a uniform transparent film, scraping the transparent film from the culture dish and grinding it to obtain a first powder; Step S4, transferring the first powder to a tube furnace, heating the temperature to 300-400° C. at a heating rate of 1-5° C. / min under a N2 atmosphere, and calcining for 1-3 hours to obtain a second powder; Step S5, transferring the second powder to a muffle furnace, heating the temperature to 350-500° C. at a heating rate of 5-10° C. / min in air, and calcining for 1-3 hours to obtain a noble metal-sensitized nanoporous SnO2 gas-sensitive material.
2. The method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material according to claim 1, characterized in that: The diol is a diol having 2 to 12 carbon atoms.
3. The method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material according to claim 1, characterized in that: The inorganic tin salt is selected from one of tin tetrachloride, stannous chloride, stannous sulfate and sodium stannate.
4. The method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material according to claim 1, characterized in that: The concentrated acid solution is one or more of concentrated hydrochloric acid, concentrated nitric acid and concentrated sulfuric acid; the amphiphilic block copolymer used is a diblock, triblock or multiblock copolymer with a number average molecular weight of 5000-60000.
5. The method for preparing the noble metal-sensitized nanoporous SnO2-based gas-sensitive material according to claim 1, characterized in that: The obtained noble metal-sensitized nanoporous SnO2-based gas-sensitive material has a specific surface area of 80 m 2 ·g -1 ~200m 2 ·g -1 , pore size is 15nm~50nm, pore volume is 0.1cm 3 ·g -1 ~1.5cm 3 ·g -1 , the size of precious metal nanoparticles is 1 to 5 nm.
Citation Information
Patent Citations
Noble metal-loaded ordered double-mesoporous metal oxide composite material and preparation method thereof
CN112225255A
Preparation method for nano precious metal particle modified tin dioxide gas sensitive material
CN102041474A
Method for preparing precious metal gold particle catalytically-grown stannic oxide nanowire
CN103043712A
Preparation method for zinc oxide / stannic oxide composite microsphere
CN103566843A
Pt-doped SnO2 mesoporous thin film-based gas sensor preparation method
CN105092659A
